Interpersonal Function in Course Webtoon Comic: A Systemic Functional Linguistics Analysis - Rudi Anshari; Dina Hanifa; Indri Octa Miransyah; Sennya x Sennya Nurditasari (Yayasan Visi Intan Permata, 2021)
The purposes of this research are to analyze the webtoon with interpersonal functions in the term of mood and residue in Webtoon Comic that can be found by the writers, and the most dominant Mood type in a webtoon entitled